Assessment and feedback: an experience of teaching innovation - Costado, Maria Teresa (Frontiers in Education, 2025)
Assessing the learning process of students is not easy, as it is difficult to verify that their learning is adequate. In this research, several individual tests are carried out to assess in a continuous, controlled, formative and summative way whether the learning process of mathematical knowledge is effective, as well as to complete this assessment with concise and individualized feedback. The more than 300 participants are students of the Primary Education Degree from four generations and two mathematical knowledge subjects. The results show that the first three generations show an average level of initial mathematical knowledge compared to the fourth control generation, increasing to an intermediate or high success rate in the intermediate tests that form part of the continuous assessment. Likewise, the final tests reflect a high cumulative performance rate, around 90%, considering this as a commitment of the student to his or her own educative process. In conclusion, the fourth generation, the control group where this controlled evaluation process has not been carried out, obtains worse academic results.